Analisis Tingkat Kesehatan Koperasi Simpan Pinjam Pada Pusat Koperasi Kartika Sriwijaya - Anisa Nur Fadillah; Indra Satriawan; Eka Jumarni Fithri (Student Research Journal, 2023)
The mission of this final report is to assess the health level of the Kartika Sriwijaya Cooperative Center, with reference to the Guidelines for Assessing the Health of Savings and Loan Cooperatives and Savings and Loan Cooperative Units as stipulated in Deputy Deputy for Supervision Regulation of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 06/Per/Dep.6/IV/2016. The data collection methods employed in this report include interview techniques and document collection. The data used consist of primary data obtained through interviews and secondary data taken from the financial reports of Kartika Sriwijaya Cooperative Center, including the Balance Sheet and Income Statement. The analysis results indicate that overall, the health level of the Kartika Sriwijaya Cooperative Center during the period 2020-2022 is categorized as "Sufficiently Healthy," with an average score of 69.78. In 2020-2021, the cooperative was in the "Under Supervision" category with a total score of approximately 65.45. However, in 2022, there was an improvement, leading the cooperative to achieve the "Sufficiently Healthy" predicate with a total score of 78.45.